2019
DOI: 10.1055/s-0039-1697016
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da vibração mecânica nas junções neuromusculares e tipo de fibra do músculo sóleo de ratas wistar ooforectomizadas

Abstract: Objective  To evaluate the neuromuscular junctions (NMJs) and the type of muscle fibers of the soleus muscle of oophorectomized Wistar rats submitted to a mechanical vibration protocol. Methods  A total of 36 randomized rats were used in the pseudo-oophorectomy without and with treatment and oophorectomy without and with treatment groups. The treatment was performed with a vibratory platform, frequency of 60 Hz and duration of 10 minutes, 3 times a week, for 4 weeks. At the end of the intervention period, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The association of treatment with vibratory platform in the recovery of muscle damage caused by oophorectomy by Peretti et al () showed recovery in the area and diameters larger and smaller after treatment, corroborating the data presented, and hormonal deprivation causes similar results to the loss of muscle mass that culminate in atrophy in animals with disuse. Hallal et al () presented in their review several training protocols in humans with vibratory platform, and this treatment method is very effective in the recovery of muscle capacity, such as improvement in contraction capacity and strength generation, after several types of injuries.…”
Section: Discussionsupporting
confidence: 66%
“…The association of treatment with vibratory platform in the recovery of muscle damage caused by oophorectomy by Peretti et al () showed recovery in the area and diameters larger and smaller after treatment, corroborating the data presented, and hormonal deprivation causes similar results to the loss of muscle mass that culminate in atrophy in animals with disuse. Hallal et al () presented in their review several training protocols in humans with vibratory platform, and this treatment method is very effective in the recovery of muscle capacity, such as improvement in contraction capacity and strength generation, after several types of injuries.…”
Section: Discussionsupporting
confidence: 66%